Practice of the Ngalaksa Tradition as a Means of Sociocultural Education in Rancakalong, Sumedang, West Java - Budi Yasri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The Ngalaksa tradition in Rancakalong District is a manifestation of the cultural identity of agricultural communities that functions as a ceremony of gratitude for harvests as well as a mechanism for strengthening social solidarity. This study aims to reveal the philosophical meaning, historical background, ritual structure, as well as the sociocultural and religious values contained in the tradition. The method used is a qualitative approach with field studies through participatory observation, in-depth interviews with traditional leaders, and documentation and literature studies. The research results show that Ngalaksa was born from historical reflection on past food crisis trauma and functions as a spiritual preventive instrument to maintain harmony between humans, nature, and God. Socioculturally, this tradition maintains mechanical solidarity through mechanisms of mutual cooperation (gotong royong), deliberation (badanten), and inclusivity of cross-generational participation. Modern adaptations such as the use of technology and formalization of organization strengthen Ngalaksa's cultural resilience amidst globalization. The research conclusion emphasizes the importance of integrating this local wisdom into formal education and digital documentation for sustainable local identity preservation.